Material didáctico lúdico "Conociendo mi naturaleza" para mejorar las habilidades cognitivas y motoras finas en los niños y niñas de 05 años en el área de ciencia y ambiente de la Institución Educativa Inicial Nº288-Rioja. - Manosalva Hurtado, Aleida (2009)
The Materials playful "Knowing my nature" is an innovation within the field of educational technology as part of teaching resources that have helped to complement the teaching and learning in interaction with children's and teachers, improving fine motor and cognitive skills in learning activities. The overall objective of this research was to demonstrate the effects produced teaching materials playful "Knowing my nature" to improve the cognitive and fine motor skills in children from 05 years in the area of Environment, Science and Educative Institution Home No. 288 "Ana Sofia Guillena Arana "in the province of Rioja. The Materials playful "Knowing my nature," is based on the theories of the theories of Piaget Game Theory History Support of Elkonin; Theory Game GROOS-Bühler, Theory of Cousinet Sociological Theory of Multiple lntelligences Gardner's Theory of Socio-Cultural learning Vigosky Theory of Ausubel's meaningful learning, and Theory of information Processing of Gagne. The research design was pre-experimental pretest and post test, with one group of studies, the group was intact. The sample consisted of 26 students. The learning experience is developed over a 07 month with appropriate learning activities designed, made to validate our research hypothesis, as evidenced by the statistical results where the calculated T (-26. 96) is higher than the critical value of the tabulated T (-1708), accepting the resulting investigation hypotheses (H1), which means that the average post test score is higher than the average pretest of the study group, in the application of didactic materials playful "Knowing my nature" enhance the development of fine motor and cognitive abilities of children of 5 years in the area of Environment, Science and Educative Institution Home No. 288 "ANA SOFIA GUILLENA Arana" in the province of Rioja.